Analisis Pengaruh Dimensi Kualitas Jasa terhadap Kepuasan Pelanggan Perpustakaan Kota Malang - Didik Priyo Sugiharto; Triana Murtiningtyas (Akutansi Bisnis & Manajemen ( ABM ), 2016)
This study was conducted to determine the relationship and the influence of the dimensions of quality of services which include tangible, Reliability, Responsiveness, Assurance, and Emphaty to customer satisfaction in using library services Malang to determine the dimensions of service quality which one has the most dominant influence on customer satisfaction in using library services Malang. Each library can maintain its existence if it can carry out its role. Generally speaking roles - roles that can be done is be a medium between users of the collection as a source of information knowledge, be institutions and cultural interest in the development of reading and generating awareness of the importance of lifelong learning. Develop communication between the user and or with the organizers so as to create collaboration, sharing of knowledge and other scientific communications and also as a motivator, mediator and facilitator for users in search, utilize and develop knowledge and experience. Also acts as an agent of change, development and human culture. According to the city library functions required to deliver high quality service services are services that can meet the needs and expectations of library users, so as to meet users' satisfaction by providing a variety of resources. Information needed both to improve the knowledge for purposes of study, as well as to help solve the problems that are in the face it.